Magnifying lenses assisted nerve- sparing radical hysterectomy and prevention of nerve plexus trauma. Issue 4 (1st July 2008) - Mantzaris, G.; Rodolakis, A.; Vlachos, G.; Athanasiou, S.; Theocharis, S.; Sotiripoulou, C H.M.; Antsaklis, A.
Abstract : The objectives of the study were to present a new approach for nerve-sparing radical hysterectomy (NSRH) with the assistance of magnifying lenses and to describe the differences in autonomic nerve plexus trauma between NSRH type III and conventional radical hysterectomy (RH) types II and III with the aid of immunohistochemistry. Eighteen women with FIGO stage IB1 –IB2 cervical cancer underwent loupes-assisted NSRH ( n = 8), RH type II ( n = 6), and RH type III ( n = 4). Biopsies were taken intraoperatively from uterosacral ligament (USL) and cardinal ligament (CL), as well as from anterior vaginal wall (AVW) and posterior vaginal wall (PVW). Immunohistochemistry was approached with the use of S-100 protein, a general nerve marker. The percentage area of immunoreactivity (PAI) was used as an objective quantitative measure of nerve fibers within the ligaments. The PAI was greater in RH-III biopsies from both USL and CL ( P < 0.001) when compared with RH-II and NSRH biopsies. For AVW and PVW, PAI differences were not statistically significant (AVW, P = 0.119; PVW, P = 0.067). Uterine-supporting ligaments represent a major pathway for autonomic nerves to the pelvic organs. As significantly more autonomic nerves are transected during the division of the uterine-supporting ligaments in RH type III, a more careful approach in the dissection of the ligaments through nerve-preserving techniques seems to be necessary in order to prevent iatrogenic intraoperative injury of the pelvic plexus and reduce or prevent postoperative complications.